SOME GENERALIZATIONS ON  -LIFTING MODULES - Shakir, Sarah; Hamad, Bahar (Iraqi Journal of Science, 2024)
In this note we study the concept  -lifting and we add some new results. Alsowe introduce weak  -lifting modules and FI- -lifting modules as twogeneralizations of  -lifting modules. We obtain some properties, characterizationsand decompositions of weak  -lifting modules and FI- -lifting modules.